Metafisika Islam Sebagai Kerangka Filosofis Pendidikan: Telaah Ontologis, Epistemologis, dan Aksiologis - Kholili Hasib; Muhammad Alwi Yusuf (MUTAADDIB : Islamic Education Journal, 2026)
Islamic education requires a solid philosophical foundation to maintain its direction amid the currents of modernity and secularism. Islamic metaphysics offers a comprehensive ontological, epistemological, and axiological basis for constructing an integrated educational system. This study aims to examine the fundamental concepts of Islamic metaphysics and their relevance as foundational principles of education. The research employs library research with a descriptive–analytical qualitative approach. The findings indicate that Islamic metaphysics is grounded in the concept of tawḥīd as the ultimate reality, from which emerge the Islamic perspectives on human nature, knowledge, and life’s purpose. Its implications for education include: (1) educational goals that integrate worldly and spiritual dimensions; (2) a holistic curriculum that harmonizes scientific knowledge with spiritual values; (3) learning methods that respect and nurture human fiṭrah; and (4) comprehensive evaluation encompassing cognitive, affective, and spiritual domains. Islamic metaphysics thus offers an alternative paradigm capable of addressing the crisis of meaning within modern education, which often tends toward materialism and pragmatism. Keywords: Islamic metaphysics, educational foundations, Islamic philosophy of education